INFLUENCE OF HYDROPHOBIZING ADDITIVES ON THE THERMAL PROPERTIES OF LIGHTWEIGHT CASES LOCATED IN AN AGGRESSIVE ENVIRONMENT - Qodirov Giyosjon Mirzajonovich (Journals Park Publishing, 2023)
The article deals with the effect of hydrophobizing additives on the thermophysical properties of expanded clay concrete.
Keywords: vapor permeability, sorption, additives, moisture, solution, salt.